NUEVA APORTACION A LOS EFECTOS DE LA HORMONA DE CRECIMIENTO SOBRE LA RESPUESTA GONADOTROPA EN LA RATA BLANCA INFANTIL - SOTO VERGARA, EDUARDO; GUTIERREZ NAVA, ROGELIO (Instituto Nacional de Nutriología, CD MEXICO, DF, MEX, 1942)
The content of vit C in ornamental Mexican plants was detd colorimetrically (indophenol), including also de-hydroascorbic acid obtained by the usual method of reduction Figures are reported for the fresh and dried material
BOL INST ESTUD MED BIOL
Keywords: APORTACION, EFECTOS, HORMONA, CRECIMIENTO, RESPUESTA, GONADOTROPA, RATA; CIENCIAS MEDICAS; PATOLOGIA; PATOLOGIA EXPERIMENTAL